Penilaian Ekowisata Mangrovesari di Kabupaten Brebes melalui Studi Kelayakan serta Perumusan Strategi Pengembangannya - Anjani, Raissa; Amru, Khaerul; Herningtyas, Wieke; Aryantie, Melania Hanny; Ikhwanuddin, Moch.; Winanti, Widiatmini Sih; Sudinda, Teddy W. (Jurnal Teknologi Lingkungan, 2024)
The potential for tourism utilization in Indonesia's coastal areas is quite high considering its geographical location, supported by its coastline and natural vegetation. Ecotourism in coastal areas needs sustainable development planning and strategies to prevent decreasing in environment quality. This study aims to assess feasibility, analyze potential and determine priority strategies in the development of Mangrovesari ecotourism in Brebes Regency. This research was conducted based on quantitative-descriptive analysis through several methods. The feasibility assessment of ecotourism development was carried out using Analisis Daerah Operasi Obyek dan Daya Tarik Wisata Alam (ADO ODTWA) methods, the potential analysis was carried out using the Strength, Weakness, Opportunity, Threat (SWOT) methods, while the determination of priority strategies was obtained through the results of the Internal Factor Analysis Strategy-External Factor Analysis Strategy (IFAS-EFAS). Based on the ADO ODTWA analysis, Mangrovesari ecotourism deserves to be further developed with a value of 80%. The potential and strategy of Mangrovesari ecotourism development have been described in the SWOT matrix. The results of IFAS-EFAS analysis show coordinates (0.710; 0.110) with position in quadrant I, which means that the Strength-Opportunity (SO) strategy was chosen to be a priority strategy for the development of Mangrovesari ecotourism. The SO strategy is carried out through optimization and improvement of the quality of tourist attractions, increased accessibility, increased cooperation for the implementation of tourism development plans, optimization of information media, as well as capacity building and community involvement.   Abstrak Potensi pemanfaatan pariwisata di kawasan pesisir Indonesia cukup tinggi mengingat letak geografisnya, didukung garis pantai dan vegetasi alamnya. Ekowisata di kawasan pesisir perlu diiringi denganperencanaan dan strategi pengembangan berkelanjutan untuk mencegah penurunan kualitas lingkungan. Penelitian ini bertujuan untuk menilai kelayakan, menganalisis potensi, serta menentukan strategi prioritas dalam pengembangan ekowisata Mangrovesari di Kabupaten Berbes. Penelitian ini dilakukan berbasis analisis deskriptif-kuantitatif melalui beberapa metode. Penilaian kelayakan  pengembangan ekowisata dilakukan menggunakan metode Analisis Daerah Operasi Objek dan Daya Tarik Wisata Alam(ADO ODTWA), analisis potensi dilakukan menggunakan metode Strength, Weakness, Opportunity, Threat (SWOT), sedangkan penentuan strategi prioritas diperoleh melalui hasil analisis Internal Factor Analysis Strategy-External Factor Analysis Strategy (IFAS-EFAS). Berdasarkan hasil analisis ADO ODTWA, ekowisata Mangrovesari layak untuk dapat dikembangkan lebih lanjut dengan nilai 80%. Potensi dan strategi pengembangan ekowisata Mangrovesari telah digambarkan dalam matriks SWOT. Hasil analisis IFAS-EFAS menunjukkan koordinat (0,710; 0,110) dengan posisi pada kuadran I, yang berarti bahwa strategi Strength-Opportunity (SO) dipilih menjadi strategi prioritas untuk pengembangan ekowisata Mangrovesari. Strategi SO dilakukan melalui optimalisasi dan peningkatan kualitas objek wisata, peningkatan aksesibilitas, peningkatan kerjasama untuk implementasi rencana pengembangan wisata, optimalisasi pemanfaatan media informasi, serta peningkatan kapasitas dan keterlibatan masyarakat.